Mentoring Relationships and Gender Inequities in Academic Medicine: Findings From a Multi-Institutional Qualitative Study. (28th December 2021) - Murphy, Marie; Record, Helena; Callander, Jacquelyn K.; Dohan, Daniel; Grandis, Jennifer R.
Abstract : Supplemental Digital Content is available in the text. Abstract : Purpose: This study examined how mentoring relationships may reinforce or mitigate gender inequities in academic medicine. Method: In-depth, semistructured interviews with medical school faculty members (52 women and 52 men) were conducted at 16 institutions across the United States in 2019. Institutions were recruited using a purposive sampling strategy to seek diversity in geography, ownership (private or public), and prestige. Within institutions, purposive sampling was used to recruit equal numbers of women and men and to seek diversity in degree type (MD, PhD), age, and career stage. A coding scheme was developed through iterative analysis of the interview transcripts. All interview transcripts were then coded with the goal of identifying intersections between mentorship and experiences of and responses to gender inequities. Results: Four key themes at the intersection of mentoring relationships and gender inequities were identified. (1) Both women and men became aware of gender inequities in academic medicine through relationships with women mentors and mentees. (2) Both women and men mentors recognized the challenges their female mentees faced and made deliberate efforts to help them navigate an inequitable environment. (3) Both women and men mentors modeled work–family balance and created family friendly environments for their mentees. (4) Some women, but no men, reported being sexually harassed by mentors. Conclusions: This study shows that mentoring relationships may be a context in which gender inequities are acknowledged and mitigated. It also shows that mentoring relationships may be a context in which gender inequities, such as sexual harassment, may occur. Sexual harassment in academic medicine has been widely documented, and gender inequity in academic medicine has proved persistent. While mentoring relationships may have the potential to identify and mitigate gender inequities, this study suggests that this potential remains largely unrealized.